Microbial bioformulation: a microbial assisted biostimulating fertilization technique for sustainable agriculture - Khan, Amir; Singh, Ajay Veer; Gautam, Shiv Shanker; Agarwal, Aparna; Punetha, Arjita; Upadhayay, Viabhav Kumar; Kukreti, Bharti; Bundela, Vindhya; Jugran, Arun Kumar; Goel, Reeta (Frontiers in Plant Science, 2023)
Addressing the pressing issues of increased food demand, declining crop productivity under varying agroclimatic conditions, and the deteriorating soil health resulting from the overuse of agricultural chemicals, requires innovative and effective strategies for the present era. Microbial bioformulation technology is a revolutionary, and eco-friendly alternative to agrochemicals that paves the way for sustainable agriculture. This technology harnesses the power of potential microbial strains and their cell-free filtrate possessing specific properties, such as phosphorus, potassium, and zinc solubilization, nitrogen fixation, siderophore production, and pathogen protection. The application of microbial bioformulations offers several remarkable advantages, including its sustainable nature, plant probiotic properties, and long-term viability, positioning it as a promising technology for the future of agriculture. To maintain the survival and viability of microbial strains, diverse carrier materials are employed to provide essential nourishment and support. Various carrier materials with their unique pros and cons are available, and choosing the most appropriate one is a key consideration, as it substantially extends the shelf life of microbial cells and maintains the overall quality of the bioinoculants. An exemplary modern bioformulation technology involves immobilizing microbial cells and utilizing cell-free filters to preserve the efficacy of bioinoculants, showcasing cutting-edge progress in this field. Moreover, the effective delivery of bioformulations in agricultural fields is another critical aspect to improve their overall efficiency. Proper and suitable application of microbial formulations is essential to boost soil fertility, preserve the soil's microbial ecology, enhance soil nutrition, and support crop physiological and biochemical processes, leading to increased yields in a sustainable manner while reducing reliance on expensive and toxic agrochemicals. This manuscript centers on exploring microbial bioformulations and their carrier materials, providing insights into the selection criteria, the development process of bioformulations, precautions, and best practices for various agricultural lands. The potential of bioformulations in promoting plant growth and defense against pathogens and diseases, while addressing biosafety concerns, is also a focal point of this study.